Prediction and minimization of NOx emission in a circulating fluidized bed combustor: Improvement of bed quality by optimizing cyclone performance and coal particle size. (15th November 2022) - Ke, Xiwei; Yao, Yuge; Huang, Zhong; Zhang, Man; Lyu, Junfu; Yang, Hairui; Zhou, Tuo
Highlights: Improvement of cyclone performance contributes to reducing the NOx emission. Reducing coal particle size can decrease the NOx emission. NOx emission may be further reduced by reducing the height of the coal inlet. Effects of cyclone efficiency and coal size on combustion efficiency are discussed. A comprehensive CFB mathematical model is applied to further analyze the mechanism. Abstract: The NOx emission of circulating fluidized bed (CFB) boilers can be evidently reduced via optimization of the cyclone performance and the coal particle size, which has been proved in industrial practices, while there are few reasonable interpretations for these phenomena so far. In this paper, a comprehensive 1-dimensional/1.5-dimensional CFB mathematical model was applied to investigate the effect of these two important factors on NOx emission. Simulation results on two commercial CFB boilers indicate that increasing the cyclone efficiency and reducing the coal particle size can significantly decrease the average size of bed materials and increase the solid suspension density in the freeboard zone; namely, the bed quality is improved. The local gas–solid flow behaviors inside the CFB furnace will be accordingly changed, such as the increasing volume fraction of bubble phase in dense bed, shortening of secondary air penetration depth, enrichment of particles in the downward-flow annulus or clusters, etc. Consequently, the reducing atmosphere will be formed or enhanced in local areas, leading to the effective inhibition of NOx formation. Meanwhile, the increase in the bed inventory of fine char particles also facilitates the reduction of NOx . Moreover, if appropriately reducing the height of the coal inlet or feeding fine coal particles from the solid recycle system, the NOx emission may be further reduced due to the adjustment of the volatiles release pattern. In addition, the reduction of coal particle size can contribute to the increase in fuel combustion efficiency, while the unburned carbon content in fly/bottom ash may increase or decrease with the improvement of cyclone efficiency. This study further analyzes the influence of gas–solid flow characteristics on the chemical reaction process and provides a new solution to the low-cost pollutant emission control for CFB boilers.